2011
DOI: 10.1891/0889-8391.25.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias in Anxiety Disorders Following Cognitive Behavioral Treatment

Abstract: A substantive literature suggests that anxious people have an attentional bias toward threatening stimuli. To date, however, no systematic review has examined the effects of cognitive behavioral therapy (CBT) for anxiety on attentional bias. A better understanding of the extant literature on CBT and its effect on attentional bias can serve to bridge the gap between experimental research on cognitive bias and the implications for clinical treatment of anxiety disorders. The present review examined studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…CBT might modify attentional bias by more than one mechanism (Tobon et al 2011). For example, one possible interpretation of the present results is that CBT may be effective in directly reducing attentional bias by teaching children strategies to reduce the extent to which they allocate attention to task-irrelevant emotional information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CBT might modify attentional bias by more than one mechanism (Tobon et al 2011). For example, one possible interpretation of the present results is that CBT may be effective in directly reducing attentional bias by teaching children strategies to reduce the extent to which they allocate attention to task-irrelevant emotional information.…”
Section: Discussionmentioning
confidence: 99%
“…Research using various experimental paradigms, such as the visual probe task (MacLeod et al 1986) and the emotional Stroop task (Mathews and MacLeod 1985), has shown that adults with clinical anxiety as well as high levels of trait anxiety have greater attentional bias for threatening material than non-anxious individuals (for review and meta-analysis of 172 studies, see Bar-Haim et al 2007). Furthermore, a review of research examining the effect of CBT on attentional bias to threat, indicates that the majority of studies found that the bias is reduced by CBT in anxious adults (Tobon et al 2011). This decrease in attention bias during CBT may be due to anxious individuals developing attention control strategies to minimize processing of negative stimuli and thoughts unrelated to current goals and activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT includes training in cognitive restructuring of maladaptive beliefs (cognitive change) and behavioral strategies such as exposure to avoided situations (situation selection) and is an effective treatment for many types of psychological problems. To a lesser degree, CBT also works toward modifying maladaptive patterns of situation modification, attentional deployment [68], and response modulation emotion-regulatory strategies. CBT is the gold-standard intervention for SAD [43].…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…In a recent review of threat perception in CBT with anxious adults, 10 of 13 studies showed reduced attentional bias after CBT [15]. However, included studies used a variety of more or less explicit experimental paradigms.…”
Section: Introductionmentioning
confidence: 99%